Modulating gastrointestinal microbiota to alleviate diarrhea in calves - Du, Wenjuan; Wang, Xianghuang; Hu, Mingyang; Hou, Jinxiu; Du, Yufeng; Si, Wenjin; Yang, Linhai; Xu, Le; Xu, Qingbiao (Frontiers in Microbiology, 2023)
The calf stage is a critical period for the development of heifers. Newborn calves have low gastrointestinal barrier function and immunity before weaning, making them highly susceptible to infection by various intestinal pathogens. Diarrhea in calves poses a significant threat to the health of young ruminants and may cause serious economic losses to livestock farms. Antibiotics are commonly used to treat diarrhea and promote calf growth, leading to bacterial resistance and increasing antibiotic residues in meat. Therefore, finding new technologies to improve the diarrhea of newborn calves is a challenge for livestock production and public health. The operation of the gut microbiota in the early stages after birth is crucial for optimizing immune function and body growth. Microbiota colonization of newborn animals is crucial for healthy development. Early intervention of the calf gastrointestinal microbiota, such as oral probiotics, fecal microbiota transplantation and rumen microbiota transplantation can effectively relieve calf diarrhea. This review focuses on the role and mechanisms of oral probiotics such as Lactobacillus, Bifidobacterium and Faecalibacterium in relieving calf diarrhea. The aim is to develop appropriate antibiotic alternatives to improve calf health in a sustainable and responsible manner, while addressing public health issues related to the use of antibiotics in livestock.